The impact of spurious collisional heating on the morphological evolution of simulated galactic discs. Issue 4 (10th January 2023) - Wilkinson, Matthew J; Ludlow, Aaron D; Lagos, Claudia del P; Fall, S Michael; Schaye, Joop; Obreschkow, Danail
ABSTRACT: We use a suite of idealized N -body simulations to study the impact of spurious heating of star particles by dark matter (DM) particles on the kinematics and morphology of simulated galactic discs. We find that spurious collisional heating leads to a systematic increase of the azimuthal velocity dispersion (σϕ ) of stellar particles and a corresponding decrease in their mean azimuthal velocities ($\overline{v}_φ$ ). The rate of heating is dictated primarily by the number of DM halo particles (or equivalently, by the DM particle mass at fixed halo mass) and by radial gradients in the local DM density along the disc; it is largely insensitive to the stellar particle mass. Galaxies within haloes resolved with fewer than ≈10 6 DM particles are particularly susceptible to spurious morphological evolution, irrespective of the total halo mass (with even more particles required to prevent heating of the galactic centre). Collisional heating transforms galactic discs from flattened structures into rounder spheroidal systems, causing them to lose rotational support in the process. It also affects the locations of galaxies in standard scaling relations that link their various properties: at fixed stellar mass, it increases the sizes of galaxies, and reduces their mean stellar rotation velocities and specific angular momenta. Our results urge caution when extrapolating simulated galaxy scaling relations to low masses where spurious collisional effects can bias their normalization, slope, and scatter.